A computational methodology to calculate the required power in disc crushers. Issue 1 (15th September 2016) - Zuñiga, J.M.; Mantari, J.L.
Abstract: This study aims to contribute to the estimation of power consumption in a disintegration process in disc crushers (fixed and mobile). The study covers the dynamic analysis of forces acting on the particles and the mobile disc. A detailed analysis of the resultant force on the particles was performed. Finally, the consumed power is calculated with the forces acting on the mobile disc. The calculated power is a key aspect in the design of disc crusher machines. Graphical abstract: